Examining project management problems in Iran and the world - Taheripour, Sahar; Sobhiyah, Mohammadhossein (International Journal of Business Management and Entrepreneurship, 2024)
Every year, many academic theses are compiled in the field of project management. The problems that are raised as the reason for carrying out theses are sometimes derived from the theoretical gap in the existing literature, and achieving the research problem that is derived from the real context of the projects has been neglected. Perhaps one of the reasons is the lack of parallel communication between university and industry. The result is that a lot of research that takes a lot of time and money from students, is not practical at that time and does not help the existing problems of industry. As a result, in this research, project management problems in Iran have been collected in 163 academic theses through searching in various databases and the participation of a number of students over five years (2017-2021) to be compared with project management problems in the executive environment of Iran’s industry. Also, university project management problems in Iran were compared with project management problems in the world (562 articles published in IJPM and PMJ journals). The results showed that Iran’s academic sector focuses more on problems such as project control, sustainability and claims, which have a good convergence with Iran’s industrial sector in some problems such as sustainability; If most of the world’s orientation is on behavioral, governance and emerging technologies problems.